2019
DOI: 10.1002/cbdv.201900381
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the Phytochemical Contents and Free Radical‐Scavenging Capacity of Capsicum annuum var. glabriusculum (Wild Piquin Chili)

Abstract: The variability in the phytochemical concentrations of Capsicum annuum var. glabriusculum has not been extensively analyzed among wild populations and ecologic niches in its phylogeographic area. This study aimed to determine the variations in the phytochemical and antioxidant contents of the wild Piquin chili. The total flavonoid content of hydroalcoholic extracts (0.06 to 0.70 mg equivalent of quercetin per gram of dry weight (mg QE/g DW)), free radical‐scavenging capacity for 2,2‐diphenyl‐1‐picrylhydrazyl (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 50 publications
0
12
0
2
Order By: Relevance
“…Once, the DPPH radical reduced and transformed into DPPH-H, and it turns colorless or light yellow [57]. In vitro, several extractions of plants have been shown to neutralize DPPH radical scavenging activity [58][59][60][61]. Hydroxyl radical is a kind of free radical produced in the process of metabolism, which is highly toxic and harmful to organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Once, the DPPH radical reduced and transformed into DPPH-H, and it turns colorless or light yellow [57]. In vitro, several extractions of plants have been shown to neutralize DPPH radical scavenging activity [58][59][60][61]. Hydroxyl radical is a kind of free radical produced in the process of metabolism, which is highly toxic and harmful to organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Among the various factors that affect the antioxidant capacity of pepper, genotype plays a key role in influencing the antioxidant compound contents of pepper (Antonious et al., 2006; Deepa et al., 2006; Farhoudi et al., 2019; Frary et al., 2008; Guil‐Guerrero et al., 2006; Meckelmann et al., 2013; Mi et al., 2022; Moreno‐Ramírez et al., 2019; Olatunji & Afolayan, 2019; Sahid et al., 2023; Tundis et al., 2011; Valková et al., 2021). Most of the studies observed variability within and among pepper genotypes for the content of antioxidant compounds.…”
Section: Factors Influencing Antioxidant Activity Of Peppermentioning
confidence: 99%
“…Several recent studies have shown the potential of pepper antioxidants to ameliorate the oxidative stress related to aging and the development of diseases, such as cancer, neurodegeneration, hyperglycemia, cardiovascular, and other diseases (Allam, 2021; Jang et al., 2022; Lavorgna et al., 2019; Lekala et al., 2019; Pannangrong et al., 2020; Sahid et al., 2023; Sinisgalli et al., 2021; Thongin et al., 2022; Thuphairo et al., 2019; Zimmer et al., 2012). On the other hand, various pre‐ and postharvest factors have also been found to influence the antioxidant capacity of peppers (Chen et al., 2022; Farhoudi et al., 2019; Kasampalis et al., 2022; Kim et al., 2021; Kovács et al., 2022; Martínez‐Ispizua et al., 2021; Moreno‐Ramírez et al., 2019; Ridzuan et al., 2019; Rybak et al., 2022; Salamatullah et al., 2022; Sinisgalli et al., 2020; Valkova et al., 2021; Yap et al., 2022). Understanding these factors may help in selecting the best genotype, cultivation conditions, and postharvest storage and processing methods for an optimum content of the antioxidant compounds in pepper, which can be used as dietary antioxidant supplements and as antioxidant preservatives or additives in spices industries.…”
Section: Introductionmentioning
confidence: 99%
“…É conhecida popularmente pelas variedades com aroma forte e peculiar que as diferenciam das demais espécies domesticadas (RIBEIRO et al, 2018) As espécies de Capsicum spp. são ricas em suas propriedades organolépticas singulares e benefícios à saúde humana (MORENO-RAMÍREZ et al, 2019). Além de serem uma das fontes vegetais mais ricas em carotenóides (β-caroteno, α-caroteno e β-criptoxantina), compostos com função antioxidantes (HASSAN et al, 2019).…”
Section: Considerações Finaisunclassified
“…Em relação à caracterização bromatológica, essa ainda não é realizada efetivamente a partir de descritores, contudo, os trabalhos publicados avaliam o potencial hidrogeniônico (pH), Sólidos Solúveis Totais (SST) e Acidez Total Titulável (ATT), entre outras características. Os estudos disponíveis concentraram-se na identificação e quantificação de capsaicinoidesum composto importante no gênero, que confere a pungência aos frutos com diversos benefícios para a saúde, sendo importante também para fins industriais, farmacêuticos dentre outros (PAULUS et al, 2017;NAVES et al, 2019).…”
Section: Caracterização Das Espécies De Capsicum Sppunclassified